SPECIES OF THE GENERA TEMORA AND TORTANUS FROM INDONESIAN COASTAL WAT - Mulyadi Mulyadi (The East Java Biological Society, 2009)
During taxonomic studies on the pelagic copepods of Indonesian waters, three species of Temora, T. discaudata Giesbrecht, 1882, T. discaudata n. var. and T. turbinata (Dana, 1849), and three species of Tortanus, T. (Tortanus) barbatus, T. (Tortanus) forcipatus and T. (Tortanus) gracilis were described and figured on specimens collected from 8 sites along Indonesian coastal waters. Descriptions, measurements and figures are given for those species, along with a review of their distribution over the world oceans, and with taxonomic remarks, ecological notes, and restricted synonymies.